MATERIAL BASIS OF ETHICAL ATTITUDE TOWARDS DESIRE IN ANCIENT EASTERN RELIGIOUS AND PHILOSOPHICAL SYSTEMS - Alushkin, S. V. (Anthropological Measurements of Philosophical Research, 2019)
Purpose of this article is to study the phenomenon of desire in Ancient Chinese and ancient Indian society, to reveal a material basis for the appearance and formation of the specific ethical attitude towards desire in the philosophical reflection of ancient thinkers. To fulfil this purpose, we should study and analyse methodology of desire studies in philosophical and psychological literature, analyse the ethical attitude towards desire in religious and philosophical texts of Chinese and Indian thinkers, understand social and economic basis of such an ethical attitude, that is to establish material basis of desire as the specific form of psychic activity and to recreate the logic of its development. Theoretical basis. Culturological and economic studies of orientalists and dialectical logic. Originality. The paper presents the analysis of the perspectives and drawbacks of different approaches in desire studies. Research of ethical attitude towards the desire in Ancient China and India allowed us to recreate the logic of social relations and the level of productive forces in that society. The ideological foundation of conservation and recreation of power and property relations was found in the religious doctrine of suppression of individual desires. The connection between desire formation and division of labour and its preservation in the religious, political and legal forms of social consciousness was shown. Methodological perspectives of dialectical logic were defined in the study of logical and historical coincidence in the further development of the phenomenon and the notion of desire. Conclusions. Analysis of modern philosophical and psychological literature has revealed methodological drawbacks in desire studies, as they are focused on studying desire’s notion, its representation or separate aspects of desire in individual psyche disregarding its inner logic and material basis of its becoming. Studies of the ethical attitude towards desire in Eastern culture have shown the consensus in desire suppression of individuals and similarities between Ancient Chinese and Indian cultures. There is shown significance and material basis of the transcendental law suppressing the desires even of the higher classes of the oriental society. The methodological approach stated in this article can be applied for further desire studies of Ancient Greece culture, Christian ethics and modern society.